2020
DOI: 10.1016/j.rmed.2020.106156
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oral corticosteroids on lung function, type-2 biomarkers and patient-reported outcomes in stable asthma: A systematic review and meta-analysis

Abstract: Accepted/In press). The effects of oral corticosteroids on lung function, type-2 biomarkers and patient-reported outcomes in stable asthma: a systematic review and meta-analysis. Respiratory Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 75 publications
0
8
1
Order By: Relevance
“…Studies of biologic-naive patients with SEA showed that prednisolone improved asthma symptoms alongside FEV 1 increase and FENO decrease. [20][21][22][23][24][25][26][27] In contrast, the current study of mepolizumab-treated patients demonstrated that asthma symptoms did not improve despite improvement in small-airway obstruction and reduction in FENO. The lack of symptom improvement after prednisolone in patients on mepolizumab is in keeping with a previous study that showed that improvements in breathlessness, wheeze, and cough measured by VAS were less in those on mepolizumab compared with those without mepolizumab.…”
Section: Discussioncontrasting
confidence: 87%
“…Studies of biologic-naive patients with SEA showed that prednisolone improved asthma symptoms alongside FEV 1 increase and FENO decrease. [20][21][22][23][24][25][26][27] In contrast, the current study of mepolizumab-treated patients demonstrated that asthma symptoms did not improve despite improvement in small-airway obstruction and reduction in FENO. The lack of symptom improvement after prednisolone in patients on mepolizumab is in keeping with a previous study that showed that improvements in breathlessness, wheeze, and cough measured by VAS were less in those on mepolizumab compared with those without mepolizumab.…”
Section: Discussioncontrasting
confidence: 87%
“…The fact that patients treated in the acute phase with corticosteroids had lower mean FeNO values than those not treated with such agents is another expected result. While we have no information on whether the use of corticosteroids was in accordance with the recommendations available for hospitalised patients with acute COVID-19 [ 30 ] because such treatment was administered in different hospital settings than in our facilities, it is known that treatment with systemic corticosteroids induces a drastic reduction in FeNO values, although in non-asthmatic subjects it is difficult to predict whether they rise again and, if so, after how long [ 31 ]. In any case, a small study found FeNO levels within the normal range during acute symptoms of SARS-CoV-2 infection, with some increase during the recovery phase, independently of disease severity or the patient's history of atopy.…”
Section: Discussionmentioning
confidence: 99%
“…33 Lastly, it must be noted that as with other Th2 biomarkers, EOS stability is affected by corticosteroid use and can be suppressed (~76%) for up to 3 months, therefore clinicians should discern whether there was recent corticosteroid use when interpreting EOS levels. 44,45 Fractional Exhaled Nitric Oxide…”
Section: Sputum and Blood Eosinophilsmentioning
confidence: 99%